Impact of oil pollution on soil properties : a case of Sable Chemical Industries - Chimhina, Chiedza M. (Midlands State University, 2020)
The study examined the impact of oil pollution on soil properties at Sable Chemical Industries. The researcher used a descriptive case study research design. The research encompassed both qualitative and quantitative research paradigms and use of primary and secondary methods of data collection. Primary data was gathered through questionnaires, direct field observations, interviews and soil sample collection while secondary data was obtained from the journals and Sable Chemical Industries SHE incident records. Data analysis was done using Statistical Package for Social Scientists (SPSS), content analysis and Microsoft Excel. The research findings identified mechanical failure, breakdown maintenance and human error as the major causes of oil spills at Sable Chemical Industries. The level of knowledge on oil handling practices amongst Sable Chemical industries’ employees is still low due to lack training and Managemental commitment. The collected soil samples were subjected to laboratory tests and the results obtained showed variations in pH, electrical conductivity and moisture content. The range of electrical conductivity of the unpolluted sites was 20-49(mS/m) compared to the 31-99(mS/m) for the polluted sites with an average of 78% increase. The soil pH drastically decreased from 7.12 (control) to 5.48 whilst the soil moisture content has decreased by 60%. Due to hydrocarbon pollution the soils have become highly acidic, compacted, negatively charged (ions) with low moisture content. The result from the chi-square test shows that there is a significant relationship (p<0.05; p=0.04) between oil pollution and physic- chemical alteration of soil properties. The research recommends Sable Chemical Industries to formulate an oil spill response team and draft an oil spill response procedure which clearly outlines the responsibilities, targets and action plans towards oil spill reduction to reduce environmental pollution. Environmental Management Agency should also educate waste oil producing entities on how to practice safe and sound waste oil disposal